The notes to methods for industrial cluster identification - Stejskal, Jan; Hájek, Petr (Univerzita Pardubice, 2009)
The conception of the regional policy and regional development is still an evolving process. The economic growth is the limelight in context of the European regional policy. The main growth determinant is also increasing competition of the municipalities, regions and countries. It can be realized thanks to engines (centres of excellence, clusters) support. These centres are the carriers of the main part of the local and regional economic development. At these levels there are many tools of local and regional development used.
Keywords: business climate; industrial clusters; Czech Republic; Regional Policy